2014
DOI: 10.1371/journal.pcbi.1003900
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Manipulation of Objects with Complex Dynamics: Predictability over Chaos

Abstract: The study of object manipulation has been largely confined to discrete tasks, where accuracy, mechanical effort, or smoothness were examined to explain subjects' preferred movements. This study investigated a rhythmic manipulation task, which involved continuous interaction with a nonlinear object that led to unpredictable object behavior. Using a simplified virtual version of the task of carrying a cup of coffee, we studied how this unpredictable object behavior affected the selected strategies. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(96 citation statements)
references
References 53 publications
(73 reference statements)
3
60
0
Order By: Relevance
“…Finally, even if not physically tiring, the incompatible and possibly unpredictable changes in velocities lead to discomfort and cognitive fatigue. A recent study showed that in complex object control, predictability of the object dynamics was a major determinant for human movement generation that outweighed the minimization of force [26]. Hence, complex interactions may introduce additional costs that are absent in unconstrained movements.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, even if not physically tiring, the incompatible and possibly unpredictable changes in velocities lead to discomfort and cognitive fatigue. A recent study showed that in complex object control, predictability of the object dynamics was a major determinant for human movement generation that outweighed the minimization of force [26]. Hence, complex interactions may introduce additional costs that are absent in unconstrained movements.…”
Section: Discussionmentioning
confidence: 99%
“…To quantitatively test this hypothesis, predictability must be operationalized. One possible measure is the mutual information (MI) between the applied force and the motion of the object, which characterizes the long-term predictability of the object’s dynamics (Cover and Thomas 2006; Nasseroleslami et al 2014). MI is a nonlinear correlation measure defined between two probability density distributions of two random variables and quantifies the information shared between the two.…”
Section: Predictable and Unpredictable Interactions—chaosmentioning
confidence: 99%
“…Our recent study provided evidence that subjects increase the predictability of object dynamics with practice and favor predictable solutions over those that minimize expended force and smoothness, criteria that are widely supported criteria for free movements (Nasseroleslami et al 2014). In this study, subjects (n = 8) oscillated the virtual cup between two targets with a robotic manipulandum, paced by a metronome at 1 Hz for 50 trials, each lasting 45 s. They were free to choose their movement amplitude and relative phase between the ball and cup.…”
Section: Predictable and Unpredictable Interactions—chaosmentioning
confidence: 99%
See 2 more Smart Citations